Monitoring dan Kendali Tegangan Jaringan Listrik Fase-tiga melalui Smartphone - Arief Goeritno; Febby Hendryan (Ikatan Ahli Informatika Indonesia (IAII), 2022)
This paper describes the creation of a minimum system for monitoring and controlling the voltage on a three-phase electrical network. Making a minimum system based on the result of previous research that has been implemented in the forms of device assembly, programming, and performance measurement. The research objectives are (i) assembling the hardware and programming based on Arduino software version 1.8.10 and (ii) measuring the minimum system performance. The research method for achieving the objective of assembling a minimum system is carried out through integrated wiring as an effort to get the hardware achievement, while for programming is an effort to get the software achievement. The implementation of the research method for measuring the performance as an effort to get the achievements of hardware and software is carried out by giving the orders to activate the paths of each phase. The result of the assembly is the integration of the Arduino UNO R3 module, Ethernet Shield type of W5100, MikroTik RouterBoard, relay modules, and Android smartphone, while the results of the programming are compiling and uploading the syntax to the Arduino module and making applications in the .apk format for a smartphone. Performance measurements are carried out by activating conditions for the three phases of phase-R, phase-S, and/or phase-T. The conclusion can be obtained, that the manufacture of a minimum system is appropriate for the fulfillment with respect to the presence of an electronic device for monitoring and controlling the voltage on a three-phase electrical network.